(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The design of subgrade pavement construction with black cotton soil [expansive soil] has always been difficult for the engineers as the structure resting on black cotton soil cracks without any warning. Black cotton soil is available in M.P, Karnataka, Maharashtra, and Andhra Pradesh in our country